2016
DOI: 10.1002/trtr.1464
|View full text |Cite
|
Sign up to set email alerts
|

Meeting Characters in Caldecotts: What Does This Mean for Today's Readers?

Abstract: We examined representations of main characters in Caldecott Award winner and honor books over the past 25 years. Each book containing a human main character was coded for the following features: culture/ethnicity, gender, age, place where character lives, time period in which the character lives, disability, religion, socioeconomic status, and language usage. Although we found some promising changes in representation across the decades, overall the main characters in contemporary Caldecott books are predominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“… Avoid limiting the search for diverse texts to those that have received awards such as the Caldecott and Newberry awards. Instead, seek books that were recognized for their representation of diverse ethnic groups, such as the Coretta Scott King Award (Boyd, Causey, & Galda, 2015; Koss, Martinez, & Johnson, 2016; McNair, 2016). Consider the authenticity of the characters’ experience to ensure that students are able to find relevance in the literature (Boyd, Causey, & Galda, 2015).…”
Section: Resultsmentioning
confidence: 99%
“… Avoid limiting the search for diverse texts to those that have received awards such as the Caldecott and Newberry awards. Instead, seek books that were recognized for their representation of diverse ethnic groups, such as the Coretta Scott King Award (Boyd, Causey, & Galda, 2015; Koss, Martinez, & Johnson, 2016; McNair, 2016). Consider the authenticity of the characters’ experience to ensure that students are able to find relevance in the literature (Boyd, Causey, & Galda, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…There are multiple benefits associated with using multicultural picture books as tools to promote racial justice in the classroom (McNair, 2016; Osorio, 2018 a,b). First, multicultural picture books can serve as mirrors, windows, and sliding doors for children (Koss, Martinez, & Johnson, 2016; McNair, 2016; Sims-Bishop, 1990). In other words, multicultural picture books provide opportunities for children from diverse racial backgrounds to have their personal and collective experiences, histories, and knowledge bases related to race affirmed and celebrated in the classroom.…”
Section: Benefits Of Using Multicultural Picture Booksmentioning
confidence: 99%
“…Lysaker, Tonge, Gaulson, and Miller () found that characters can foster social imagination by helping readers learn how to better live in the world beyond the book. If characters are to serve in these ways, readers must connect to and follow them willingly into and through stories (Koss, Martinez, & Johnson, ).…”
Section: The Importance Of Charactersmentioning
confidence: 99%